ANALYSIS OF TRAINING AND DEVELOPMENT ON THE PERFORMANCE OF NON-MEDICAL EMPLOYEES AT H. ADAM MALIK HOSPITAL MEDAN - Ade Chairunnisa; Ahmad Azmi (RADJA PUBLIKA, 2024)
The aim of this research is to see the effect of training and development on the performance of non-medical employees at H. Adam Malik Hospital. The method used in this research is a quantitative method. The population in this study was all administrative employees (non-medical) at H. Adam Malik General Hospital, totaling 488 people. Meanwhile, for the sample, researchers used Random Samples Based on Area or Region (Cluster Random Sampling). Based on the results of data analysis, it can be concluded that from the research results it can be concluded that there is a positive influence between training on employee performance, there is a positive influence between development on employee performance, there is a positive and significant influence between training and development on the performance of non-medical employees at H. Adam General Hospital. Malik Medan and the coefficient of determination (R square) is 0.595, which means that 59.5% of the training and development variables can explain the high performance of employees